Survival in Critical Care Patients with COVID-19 Pneumonia: A Single Center Based Observational Study - Bam, Niraj; Bam, Niraj; Kuikel, Sandip; Sapkota, Dharmendra; Poudel, Sagar; Pant, Pankaj; Das, Santa K (Journal of Institute of Medicine Nepal, 2022)
Introduction The severity of COVID-19 pneumonia ranges from asymptomatic to requiring mechanical support for survival. This observational study describes the demographic, management, vaccination status and outcome in Nepalese patients with COVID-19 who were admitted to critical care settings. Methods Single center based cross sectional study was conducted. All the patients admitted to ICU/MICU/HDU/ICCU/SICU of Tribhuvan University Teaching Hospital were eligible subjects for this study. Demographic, clinical details and vaccination status of respective patients was abstracted from interview and chart review. Data was collected in Microsoft Excel (Ver. 2016) and statistical analysis was performed using statistical software SPSS. Results A total of 342 patients with mean age 53.95±15.6 were included in the study. The mean duration of stay in critical care was 6.74±4.43. Fever and shortness of breath was the predominant symptom present in the studied patients with all patients having shortness of breath. Out of the 342 patients, 20.2% (n=69) were intubated at least once during their critical care stay, 57.89%(n=198) received only non-invasive ventilation and 21.9% (n=75) received oxygen via other means. The overall survival rate of patients admitted to critical care of TUTH was 60.53% with very low survival rate in intubated patients. Only 8.8% of the included patients had received at least one dose of vaccine. Conclusion Our study suggest that the prognosis of critical care COVID-19 patients is poor with highest mortality in patients receiving mechanical ventilation. Delay in intubation may contribute to this worse outcome in intubated COVID-19 patients.